(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Social marketing in its non-profit dimension has always been present in the history of humanity. Non-profit organizations have been affected in recent years, due to the decrease in resources and the ignorance of them, for the most part, by the society where they operate, largely due to the lack of marketing strategies. These organizations consider the satisfaction of the consumer/user and the donor, not only in the short term, but also in the long term, and to the individual satisfaction of these figures is added the search for collective satisfaction or the well-being of society as a whole. There are different types of non-profit organizations: health, political, religious, educational, social, ecological, etc. All of them focus on trying to help solve and address problems in society and for their survival, they require donations, sponsorships and volunteers. Social responsibility is a collective behavior and within that collective behavior, one of the actors is society. The objective of this research is to know the awareness that Morelia society has of these organizations, and their involvement, in order to determine the appropriate marketing strategies so that these types of organizations are better known because very few know of their existence and their form of operation, therefore, little participate in them; With the implementation of marketing strategies, you can achieve greater participation from society, as many are interested in participating in its different forms. There are various organizations that defend different causes and address various problems that are relevant in society, and that society itself is willing to support. This research is exploratory, experimental and descriptive, based on documentary analysis of scientific articles, popular articles and books; as well as the use of a survey instrument, to show the findings and conclude the investigation.